Depression effects on hospital cost of heart failure patients in California: An analysis by ethnicity and gender - Baqar A Husaini; Deborah Taira; Keith Norris; S Vivek Adhish; Majaz Moonis; Robert Levine (Wolters Kluwer Medknow Publications, 2018)
Background: Depression often interferes with self-management and treatment of medical conditions. This may result in serious medical complications and escalated health-care cost. Objectives: Study distribution of heart failure (HF) cases estimates the prevalence of depression and its effects on HF-related hospital costs by ethnicity and gender. Methods: Secondary data files of California Hospital Discharge System for he year 2010 were examined. For patients with a HF diagnosis, details regarding depression, demographics, comorbid conditions, and hospital costs were studied. Age-adjusted HF rates and depression were examined for whites, blacks, Hispanics, and Asians/Pacific Islanders (AP) by comparing HF patients with depression (HF +D) versus HF without depression (HFND). Results: HF cases (n = 62,685; average age: 73) included nearly an equal number of males and females. HF rates were higher (P < 0.001) among blacks compared to Hispanics, AP, and whites and higher among males than females. One-fifth of HF patients had depression, higher among females and whites compared to males and other ethnic groups. Further, HF hospital costs for blacks and AP were higher (P < 0.001) compared to other groups. The cost for HF +D was 22% higher compared to HFND, across all gender and ethnic groups, largely due to higher comorbidities, more admissions, and longer hospitalization. Conclusion: Depression, ethnicity, and gender are all associated with increased hospital costs of HF patients. The higher HF and HF +D costs among blacks, AP, and males reflect additional burden of comorbidities (hypertension and diabetes). Prospective studies to assess if selective screening and treating depression among HF patients can reduce hospital costs are warranted.